The unity of mathematics: a casebook comprising practical geometry number theory and linear algebra - Hilton, Peter; Pedersen, Jean (Teaching Mathematics and Computer Science, 2003)
We give a sustained example, drawn largely from earlier publications, of how we may freely pursue a line of mathematical enquiry if we are not constrained, unnaturally, to confine ourselves to a single mathematical subdiscipline; and we draw conclusions from the study of this example which are relevant at many levels of mathematical instruction.We also include the statement and proof of a new result (Theorem 4.1) in linear algebra which is obviously fundamental to the geometrical investigation which constitutes the leit-motif of the paper.